Penerapan Deep Learning untuk Prediksi Kasus Aktif Covid-19 - Syafa’ah, Lailis; Lestandy, Merinda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Coronavirus disease (Covid-19) is increasingly spreading in Indonesia, so it requires an approach to predict its spread. One approach method that is often used is the Deep Learning (DL) method. DL is a branch of Machine Learning (ML) which is modeled based on the human nervous system. In this study, the prediction of active Covid-19 cases was resolved using the DL method. The dataset used is 260 data with 10 parameters. DL is able to provide an accurate prediction of active cases of Covid-19 with an MSE of 0.032 and an accuracy of 81.333%.